2020
DOI: 10.1371/journal.pone.0229338
|View full text |Cite
|
Sign up to set email alerts
|

The global variation of medical student engagement in teaching: Implications for medical electives

Abstract: Introduction International medical electives, whereby undergraduates visit an institution in a country other than their own, are a common part of medical training. Visiting students are often asked to provide local teaching, which may be acceptable where the visitor is acting within the bounds of their own competency and the normal practices of both their home and host institutions. However, the extent to which teaching is an accepted student activity globally has not previously been described. This study aims… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…The second group consisted of publications written by members of host institutions in LMICs, or based on interviews with them (5 papers) [2,25,28,35,36]. The third group was publications which were produced by neither of these groups, consisting primarily of editorials, systematic reviews, and guidelines written by universities (18 papers) [5][6][7][9][10][11][12][13][14]21,23,30,[37][38][39][40][41][42].…”
Section: Literature Selection Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second group consisted of publications written by members of host institutions in LMICs, or based on interviews with them (5 papers) [2,25,28,35,36]. The third group was publications which were produced by neither of these groups, consisting primarily of editorials, systematic reviews, and guidelines written by universities (18 papers) [5][6][7][9][10][11][12][13][14]21,23,30,[37][38][39][40][41][42].…”
Section: Literature Selection Resultsmentioning
confidence: 99%
“…Secondly, steps could be undertaken by institutions to make exchange programmes mutually bene cial. This could be achieved through including members of host institutions in research collaborations, abstract or poster presentations [21], or peer-to-peer teaching [42]. Moreover, interviews with members of host institutions showed that the opportunity to send their own students to the institutions from which they are receiving visiting students would be the main improvement [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite evidence that UME programs routinely engage students in teaching roles, students are often not formally prepared for their teaching responsibilities. 5–7,48 Most SaT curricula identified in our literature review were offered as elective courses. Given that some UME accrediting bodies have identified teaching as a training expectation, 52–54 providing this training optionally or engaging students in teaching roles without prior training does not ensure widespread preparedness for future teaching roles.…”
Section: Discussionmentioning
confidence: 99%